Global assessment of relationships between climate and tree growth - Martin Wilmking; Marieke van der Maaten‐Theunissen; Ernst van der Maaten; Tobias Scharnweber; Allan Buras; Christine Biermann; Marina Gurskaya; Martin Hallinger; Jelena Lange; Rohan Shetti; Marko Smiljanic; Mario Trouillier (Global Change Biology, 2020)
Tree‐ring records provide global high‐resolution information on tree‐species responses to global change, forest carbon and water dynamics, and past climate variability and extremes. The underlying assumption is a stationary (time‐stable), quasi‐linear relationship between tree growth and environment, which however conflicts with basic ecological and evolutionary theory. Indeed, our global assessment of the relevant tree‐ring literature demonstrates non‐stationarity in the majority of tested cases, not limited to specific proxies, environmental parameters, regions or species. Non‐stationarity likely represents the general nature of the relationship between tree‐growth proxies and environment. Studies assuming stationarity however score two times more citations influencing other fields of science and the science–policy interface. To reconcile ecological reality with the application of tree‐ring proxies for climate or environmental estimates, we provide a clarification of the stationarity concept, propose a simple confidence framework for the re‐evaluation of existing studies and recommend the use of a new statistical tool to detect non‐stationarity in tree‐ring proxies. Our contribution is meant to stimulate and facilitate discussion in light of our results to help increase confidence in tree‐ring‐based climate and environmental estimates for science, the public and policymakers.

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

Publisher Correction to: Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome - Isabel C. Barrio; Elin Lindén; Mariska Te Beest; Johan Olofsson; Adrian Rocha; Eeva M. Soininen; Juha M. Alatalo; Tommi Andersson; Ashley Asmus; Julia Boike; Kari Anne Bråthen; John P. Bryant; et al. (Polar Biology, 2018)

Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome - Isabel C. Barrio; Elin Lindén; Mariska Te Beest; Johan Olofsson; Adrian Rocha; Eeva M. Soininen; Juha M. Alatalo; Tommi Andersson; Ashley Asmus; Julia Boike; Kari Anne Bråthen; John P. Bryant; et al. (Polar Biology, 2017)

Shrubs tracing sea surface temperature—Calluna vulgaris on the Faroe Islands - Ilka Beil; Allan Buras; Martin Hallinger; Marko Smiljanić; Martin Wilmking (International Journal of Biometeorology, 2015)

Landscape Heterogeneity of Shrub Expansion in Arctic Alaska - Ken D. Tape; Martin Hallinger; Jeffrey M. Welker; Roger W. Ruess (Ecosystems, 2012)